1991
DOI: 10.1029/91jb01639
|View full text |Cite
|
Sign up to set email alerts
|

Rock‐buffered fluid‐rock interaction in deformed quartz‐rich turbidite sequences, eastern Australia

Abstract: Quartz vein 18O/16O ratios across a 500 km transect through the Lachlan fold belt of southeastern Australia are remarkably uniform (±1–1.5 permil) at both local (centimeter to meter) and regional (over 104 km2) scales. They define isotopic zones that correlate with the tectonic divisions of the Cambrian through Devonian (dominantly Ordovician) quartz‐rich turbidites determined by regional mapping. From west to east these divisions are (1) Stawell, δ18O=14.7±1.1 (47 samples); (2) Bendigo‐Ballarat, δ18O=17.5±1.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(49 citation statements)
references
References 64 publications
2
46
1
Order By: Relevance
“…This observation is in agreement with a small-scale (ten centimetres to a few metres) migration of selected elements from wallrock to vein (compare Burkhard and Kerrich, 1988;Gray et al, 1991). This element transfer leading to vein formation could be accounted for by ionic diffusion processes.…”
Section: Major-and Trace-element Systematicssupporting
confidence: 74%
“…This observation is in agreement with a small-scale (ten centimetres to a few metres) migration of selected elements from wallrock to vein (compare Burkhard and Kerrich, 1988;Gray et al, 1991). This element transfer leading to vein formation could be accounted for by ionic diffusion processes.…”
Section: Major-and Trace-element Systematicssupporting
confidence: 74%
“…For example, Marquer and Burkhard [1992] interpreted isotope depletions in shallow level (200°-300°C), carbonate hosted late stage veins and mylonites in the Swiss Alps as evidence that kilometer-scale interconnectivity between shear zones promoted fluid expulsion upward from crystalline basement. In contrast, other case studies infer that regional deformation by pressure solution and faulting need not be accompanied by extreme volume loss or a large time-integrated fluid flux [e.g., Gray et al, 1991;Cartwright et al, 1994;Kirschner and Kennedy, 2001]. On the basis of low isotopic variation between fault rocks and their adjacent protolith, Kirschner and Kennedy [2001] found no evidence for extensive fluid advection outside of very narrow shear zones in the Front Ranges of the Canadian Rockies.…”
Section: à2mentioning
confidence: 94%
“…On the basis of low isotopic variation between fault rocks and their adjacent protolith, Kirschner and Kennedy [2001] found no evidence for extensive fluid advection outside of very narrow shear zones in the Front Ranges of the Canadian Rockies. In a dramatic example from the Lachlan fold belt of southeastern Australia, Gray et al [1991] demonstrated that diffusion and advection over relatively short distances (tens to hundreds of meters) combined to promote the isotopic homogenization of quartz veins in thrust sheets and faults across 80,000 km 2 .…”
Section: à2mentioning
confidence: 99%
“…Oliver 1986Oliver , 1992Moore and Vrolijk 1992). However, several studies of synkinematic veins at the deformation front of mature basins indicate a closed system, where fluids are mainly derived from and buffered by the wall rock (Gray et al 1991;Marquer and Burkhard 1992). During burial, the carbon and oxygen isotopic ratios increase due to intense water-rock interaction Ayalon 1987, 1991).…”
Section: Introductionmentioning
confidence: 95%